Handbook of research on emerging developments and environmental impacts of ecological chemistry - Duca, Gheorghe 1952-; Vaseashta, A. (IGI Global, 2019)
"This book examines the environmental impacts of ecological chemistry"--
Description based on title screen (IGI Global, viewed 04/15/2020)
Keywords: Green chemistry